Tropical Deforestation as an International Externality: The Property Right Issue - Murniningtyas, Endah (UI Scholars Hub, 2021)
The developing countries frequently blamed as a party who did the deforestation or do the forest logging. The developed countries try to give a penalty the developing countries with inserting environmental values to trade values. It caused a dispute between the parties because the developing countries highly dependent with the production of the major commodity, whose derived from the forest. In general, approved that the use of natural resources should pay attention the impact to the environment, either it is domestic or global environment. The universal environmental regulation and the environment whose adjusted with the boundaries in trade, in one side, it is not efficient and effective in dealing with international environmental problems, in the connection with the intellectual property rights related to the profit from tropical forests. This article gave a point of view regarding with deforestation from the viewpoint of developing countries and offer a new value which can apply to the developing country needs and global society.